Grounding Physicalism - (:unkn) unknown (My University, 2017)
Grounding physicalism is the thesis that fundamental physical truths ground every other truth. Ted Sider and Shamik Dasgupta have recently put forward a serious challenge to grounding physicalism. The challenge is an instance of a more general challenge concerning what grounds grounding facts, which has been powerfully presented by Karen Bennett. If A is some fundamental fact about physics that grounds some fact B about mental states, then what grounds the fact that A grounds B? The grounding physicalist who says that such facts are either grounded or ungrounded seems to face a dilemma: Either grounding facts are grounded and there is an infinite regress of grounding facts, or they are ungrounded and grounding physicalism is false. I reject the dilemma. I argue that grounding facts are ungrounded and that this view is consistent with grounding physicalism. I argue that rival views that say grounding facts are grounded fail.
Keywords: Explanation; Fundamentality; Grounding; Physicalism; Priority; Regress